How art works - Bray, George; Gordon, Theodore; Hand, Alison; Hodge, Susie, 1960-; Kahn, Natasha, 1973- (DK Publishing, 2022)
"An art book like no other, How Art Works uses practical graphics to demonstrate the techniques, styles, materials, and concepts that lie behind great art. It shows you how to interpret paintings, drawings, and sculptures, and reveals how art is made, laying out the key techniques and materials in visual detail. It also explains the nuts and bolts of the technical aspects behind art, such as perspective and composition, and shows how to identify major artistic styles and movements"--